Proxy Advisory Firms, Governance, Market Failure, and Regulation - Spatt, Chester S. (The Review of Corporate Finance Studies, 2021)
Abstract Proxy advisory firms developed due to market failures underlying voting and corporate governance more broadly. However, these firms, which have not been subject to mandatory regulation, reflect their own market failures, emphasizing challenges underlying corporate governance. We highlight underlying frictions, such as economies of scale and public goods aspects to information production, the import of incentive conflicts faced by the advisory firms, their power, and the implications of their recommendations and votes by different types of investors. Asset managers emphasizing stewardship are more supportive of management than are proxy advisors. We highlight the evolving regulatory environment and limitations of one-size-fits-all recommendations. (JEL G34, G38, G24, H4) Received October 31, 2019; editorial decision October 17, 2020 by Editor Andrew Ellul.